1993
DOI: 10.1046/j.1524-475x.1993.10106.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo analysis of the inability of fetal rabbit wounds to contract

Abstract: Fetal rabbit wounds that are sutured show excellent repair without obvious scarring. In contrast, an unsutured wound in a rabbit fetus does not close, and it appears that the process of wound contraction does not occur. Experiments were carried out to illustrate the mechanisms responsible for the noncontraction of open fetal rabbit wounds. Results showed that the lack of wound contraction was not an artifact caused by rapid fetal growth. With regard to the ability of cultured fetal fibroblasts to show cytoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Cellular mechanisms whereby open full-thickness excision wounds in adult mammalian skin are closed spontaneously are speculative (1)(2)(3)(4)(5)(6). The currently prevailing hypothesis (6,7), originally stated in 1956 (8,9), proposes that the central granulation tissue generated shortly after wounding is a contractile machine that, through an undefined action of its fibroblasts, pulls the edges of the wound together.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cellular mechanisms whereby open full-thickness excision wounds in adult mammalian skin are closed spontaneously are speculative (1)(2)(3)(4)(5)(6). The currently prevailing hypothesis (6,7), originally stated in 1956 (8,9), proposes that the central granulation tissue generated shortly after wounding is a contractile machine that, through an undefined action of its fibroblasts, pulls the edges of the wound together.…”
mentioning
confidence: 99%
“…The currently prevailing hypothesis (6,7), originally stated in 1956 (8,9), proposes that the central granulation tissue generated shortly after wounding is a contractile machine that, through an undefined action of its fibroblasts, pulls the edges of the wound together. Recent papers on the subject (4,7,10,11) promulgate the idea that a significant fraction of the mesenchymal cells of the granulation tissues, called myofibroblasts (12), have contractile powers that are exerted on collagen fibers, other matrix components, and each other.…”
mentioning
confidence: 99%
“…Fetal dermal wounds heal much faster and regain their natural structure and function including skin appendages and sebaceous glands [14]. α-SMA-containing fibroblasts are not present in fetal wounds or are only transiently expressed [15], and these wounds close with minimal contraction [16]. Fetal wounds are characterized by a diminished inflammatory response resulting in decreased TGF-β1 expression and altered collagen production [17].…”
Section: The Role Of Fibroblasts In Wound Healingmentioning
confidence: 99%
“…The collagen in the regenerated skin was identified as human indicating that it was produced by the fetal fibroblasts. In contrast, the transplantation of adult sheep skin into the backs of fetal lambs and later wounded healed with scars despite exposure to amniotic fluid rich in growth factors and ECM components originally thought to be important for scarless repair [24, 25, 16]. These results suggested that scarless healing is an intrinsic property of fetal skin that is orchestrated by fetal fibroblasts.…”
Section: The Fetal Fibroblastmentioning
confidence: 99%
See 1 more Smart Citation